Redescription of the genus Opisthoncus L. Koch, 1880 (Araneae: Salticidae) - Gardzińska, Joanna; Żabka, Marek (Zootaxa, 2013)
Of 33 nominal species listed by Platnick (2012), 25 species of the genus Opisthoncus are redefined and redescribed here. O. kochi Żabka, 1991, was redescribed by Prószyński (1983) while O. delectabilis Rainbow, 1920, O. eriognathus (Thorell, 1881), O. inconspicuus (Thorell, 1881), O. nigritifemur Strand, 1911 and O. pallidulus L. Koch, 1880 are excluded from the genus. O. clarus Keyserling, 1883 (the type specimen lost) is considered nomen dubium and O. verisimilis Peckham & Peckham, 1901 was not studied (types not located).